THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) TO ALLEVIATE POVERTY IN BANGLADESH - Chowdhury, Md. Shahnur Azad; Chowdhury, Mustafa Manir; Chowdhury, Nazneen Jahan; Hossain, Mohammad Emdad; Ahsan, Sayed Md. Hashib (American International Journal of Social Science Research, 2021)
Poverty is one of the problems in third-world countries like Bangladesh. There has been an ongoing battle against challenging living conditions-overcrowding, floods, deforestation, erosion, soil depletion, and natural calamities. Quite a lot of programs have been tried since the independence of Bangladesh in 1971, and to tell the truth, most have failed. Each time an anti-poverty program fails, it gives more fuel to the richer class to argue that there’s no point in trying to help the poor. However, this is an age of information technology. Almost all of the spheres of human life are contributed by Information technology. Information Technology can change the fate of the poor by helping them to be with the current time and happenings by ensuring their capabilities to access information. The Government of Bangladesh also realizes the importance of the issue, and recently they concentrated on transforming the government services to digitize. As one of the initiatives to empower the poor with information, GOB has launched Union Information and Service Centre (UISC) in all of the Union councils of the country. The private sector started digitization of operations earlier than the government. Now, as the government has also initiated the process, the journey will get a smooth and parallel speed to develop the socio-economic condition of the poor of the country. This paper attempts to explore the capabilities of ICT to reduce poverty in Bangladesh. The study will also try to suggest how ICT can be better used to eradicate poverty. ICT is a rapidly growing field in Bangladesh in recent times. The contribution of ICT in every sector of the country is trying to be addressed to improve the situation. This study is conducted by reviewing the studies in this line to suggest better policies to be formulated. The results show that ICT has excellent capabilities to alleviate poverty despite many challenges to be faced.